Statin use in adults at high risk of cardiovascular disease mortality: cross-sectional analysis of baseline data from The Irish Longitudinal Study on Ageing (TILDA). Issue 7 (13th July 2015) - Murphy, Catriona; Bennett, Kathleen; Fahey, Tom; Shelley, Emer; Graham, Ian; Kenny, Rose Anne
Abstract : Objectives: This study aims to examine the extent to which statins are used by adults at high risk of cardiovascular disease (CVD) compared to European clinical guidelines. The high-risk groups examined are those with (1) known CVD, (2) known diabetes and (3) a high or very high risk (≥5%) of CVD mortality based on Systematic COronary Risk Evaluation (SCORE). Design: This study is cross-sectional in design using data from the first wave (2009–2011) of The Irish Longitudinal Study on Ageing (TILDA). Setting and participants: The sample (n=3372) is representative of community living adults aged 50–64 years in Ireland. Results: Statins were used by 68.6% (95% CI 61.5% to 75.8%) of those with known CVD, 57.4% (95% CI 49.1% to 65.7%) of those with known diabetes and by 19.7% (95% CI 13.0% to 26.3%) of adults with a SCORE risk ≥5%. Over a third (38.5%, 95% CI 31.0% to 46.0%) of those with known CVD, 46.8% (95% CI 38.4% to 55.1%) of those with known diabetes and 85.2% (95% CI 79.3% to 91.1%) of those with a SCORE risk ≥5% were at or above the low-density lipoprotein cholesterol (LDL-C) target of 2.5 mmol/L specified in the 2007 European guidelines. Conclusions: Despite strong evidence and clinical guidelines recommending the use of statins for secondary prevention, a gap exists between guidelines and practice in this cohort. It is also of concern that a low proportion of adults with a SCORE risk ≥5% were taking statins. A policy response that strengthens secondary prevention, and improves risk assessment and shared decision-making in the primary prevention of CVD is required.